Clonal hematopoiesis onset in chronic myeloid leukemia patients developing an adverse cardiovascular event. (April 2023) - Tarantini, Francesco; Cumbo, Cosimo; Zagaria, Antonella; Anelli, Luisa; Parciante, Elisa; Redavid, Immacolata; Coccaro, Nicoletta; Tota, Giuseppina; Conserva, Maria Rosa; Minervini, Crescenzio Francesco; Minervini, Angela; Attolico, Immacolata; et al.
Abstract: Life expectation of chronic myeloid leukemia patients in the tyrosine kinase inhibitors era is almost equal to that of healthy subjects. On the other hand, their long-term management must take into account a higher risk of adverse events, at least partly related to the treatment. Various studies reported a higher incidence of cardiovascular events in these patients. Clonal hematopoiesis is broadly considered a major independent risk factor for cardiovascular events. Of note,  the underlying physiopathological mechanisms connect clonal hematopoiesis with a global proinflammatory status, triggering a vicious circle in which the somatic mutations and inflammation feed each other. All this considered, we investigated the occurrence of clonal hematopoiesis in chronic myeloid leukemia patients developing a cardiovascular event under tyrosine kinase inhibitor therapy. Highlights: Chronic myeloid leukemia (CML) long-term management is an emerging clinical issue. Cardiovascular (CV) adverse events are recognized in CML patients on TKI therapy. Clonal hematopoiesis (CH) could arise during the disease. The vicious cycle of inflammation, CH and CV events needs to be considered.